Photodynamic therapy in glioblastoma: Detection of intraoperative inadvertent 5-ALA mediated photodynamic therapeutical effect after gross total resection - Ferrés, Abel; Di Somma, Alberto; Mosteiro, Alejandra; Topczewski, Thomaz Eduardo; Roldán, Pedro; Pedrosa, Leire; Diao, Diouldé; Pineda, Estela; Sierra, Àngels; Enseñat, Joaquim; González-Sánchez, José Juan (Frontiers in Oncology, 2022)
Glioblastoma (GBM) remains the most frequent and lethal primary brain tumor in adults, despite advancements in surgical resection techniques and adjuvant chemo- and radiotherapy. The most frequent recurrence pattern (75-90%) occurs in the form of continuous growth from the border of the surgical cavity, thus emphasizing the need for locoregional tumor control. Fluorescence-guided surgical resection using 5-ALA has been widely implemented in surgical protocols for such tumors. Recent literature also highlights the applicability of 5-ALA-mediated photodynamic therapy to obtain locoregional tumor control further. This study aims to identify if 5-ALA mediated photodynamic therapeutic effect after gross total glioblastoma resection has inadvertently occurred due to the exposition of protoporphyrin IX charged peripheral tumoral cells to operative room light sources. Of 146 patients who were intervened from glioblastoma between 2015 and 2020, 33 were included in the present study. Strict gross total resection (without supralocal resection) had been accomplished, and adjuvant chemoradiotherapy protocol was administered. Two comparison groups were created regarding the location of the recurrence (group A: up to 1 centimeter from the surgical cavity, and group B: beyond 1 centimeter from the surgical cavity). The cutoff point was determined to be 1 centimeter because of the visible light penetrance to the normal brain tissue. In univariate analysis, both groups only differed regarding 5-ALA administration, which was significantly related to a minor relative risk of presenting the recurrence within the first centimeter from the surgical cavity (Relative Risk = 0,655 (95% CI 0,442-0,970), p-value=0,046). Results obtained in univariate analysis were corroborated posteriorly in multivariate analysis (RR=0,730 (95% CI 0,340-0,980), p=0,017). In the present study, a probable inadvertent 5-ALA photodynamic therapeutical effect has been detected in vivo.